Tobacco companies legally licensed to kill - Abd Razak, Dzulkifli (2008)
LATE last month, when his deputy allegedly said that "doctors are licensed to kill", the minister of health was quick to dissociate himself from the statement and throw his support behind the doctors. Indeed, this was a wise thing to do because there is little to support such an "allegation". All health professionals subscribe to the principle: "first do no harm"... But what if there is sufficient evidence? What if it is the tobacco industry? One wonders if the minister would react the same way. Evidence abounds that "tobacco kills" and that those licensed to sell tobaccorelated products are literally therefore "licensed to kill".